Gut commensals, dysbiosis, and immune response imbalance in the pathogenesis of multiple sclerosis. (May 2021) - Brown, Jordan; Quattrochi, Blair; Everett, Colleen; Hong, Bo-Young; Cervantes, Jorge
Intestinal microbiota alterations have been found to be directly related to a wide range of disease states in humans, including multiple sclerosis (MS). The etiology of MS is highly debated and subsequently, there is no cure. Research dedicated to MS and its murine model, experimental autoimmune encephalomyelitis (EAE), have found that dysbiosis of the gut microbiota may play a role in the disease state and severity. In this review, we discuss the characteristic dysbiosis in MS, the role commensal-derived ligands may have in the pathogenesis of the disease, and the possibility of targeting the microbiota as a future therapy.